In vitro study of the effects of Angiostrongylus cantonensis larvae extracts on apoptosis and dysfunction in the blood-brain barrier (BBB). - Xin Hu; Jiang-Hui Li; Lan Lan; Fei-Fei Wu; Er-Peng Zhang; Zeng-Mei Song; Hui-Cong Huang; Fang-Jun Luo; Chang-Wang Pan; Feng Tan (PLoS ONE, 2012)
It has been hypothesized that blood-brain barrier (BBB) dysfunction in Angiostrongylus cantonensis infection might be due to the apoptosis of the hosts' BBB cells. Here, we evaluated this hypothesis through several methods, all based on an in vitro mouse BBB model consisting of primary culture brain microvascular endothelial cells (BMECs) and brain astrocytic cells (BACs). In the present study, a four-hour percolation and HRP permeability experiment showed that A. cantonensis larvae extracts can increase the permeability of the BBB. Apoptosis among BMECs and BACs after exposure to larvae extracts was monitored by TUNEL and annexin-V-FITC/PI double staining. A. cantonensis larvae extracts were found to induce apoptosis in both BMECs and BACs. For this reason, we concluded that the induction of apoptosis might participate in the BBB dysfunction observed during angiostrongyliasis. Improved fundamental understanding of how A. cantonensis induces apoptosis may lead to new approaches to the treatment or prevention of this parasitic disease.